Substantiating the design of equipment for preparing oil and gas field products for transportation - Nesterenko, Tetiana; Nazarenko, Ivan; Nesterenko, Mykola; Shevchenko, Oleksandr; Khyzhniak, Andrii; Bernyk, Iryna; Onyshchenko, Artur; Moshkivskyi, Roman (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates processes that separate gas-liquid flows and purify formation water in the equipment for oil and gas field production preparation units. At the late stage of field development, the efficiency of separation depends on the ability of the equipment to operate under conditions of waterlogging, an increase in the content of mechanical impurities, and a decrease in formation pressure. Under such conditions, conventional separation equipment does not provide the required quality of hydrocarbon separation and purification of formation water. The task addressed in this work has been solved by improving the internal structural elements in the three-phase separator and a cyclone in the hydrocarbon preparation unit. Hydraulic losses were within permissible values; no secondary removal of drops into the gas stream occurred. That was confirmed by the results of thermodynamic and CFD modeling. This is a feature of the approach in comparison with those reported in which studies of new design solutions were not comprehensively conducted. The issues of hydraulic losses and secondary removal of drops into the gas stream remained open. The design solutions proposed in this work affected the separation efficiency – the volume of the selected condensate increased while the total hydraulic losses did not exceed 0.037 MPa. It has been proven that new structural solutions for separation elements provide a more uniform distribution of speeds and form local zones with reduced speeds. The results are explained by a change in the flow structure, an increase in inertial deposition of drops, and a decrease in low-mobility zones in the flow part of the separation elements. The findings could be implemented in the reconstruction of oil and gas treatment plants, in the design of internal separation elements, and when choosing structural solutions for cyclones in order to purify formation water